Audit Sistem Informasi Pengantaran Barang Pada PT Samudera Arkan Nusantara Menggunakan Framework COBIT 4.1 - Akbar, Dimas; Juliana; Mulia, Sri; Ningrum, Widya; Syahputra, Andrian (Journal of Digital Ecosystem for Natural Sustainability, 2022)
This study will discuss how to audit the information system for delivery of goods at PT Samudera Arkan Nusantara uses COBIT 4.1 sub domains PO, AI, DS, ME. Data were collected using interviews and questionnaires. Questions from the questionnaire are made based on the activities of customers who want to deliver goods at PT Samudera Arkan Nusantara. The results showed that the results of the questionnaire management got the average value for the domains PO, ME, A|, DS was 7.07 and ranged 0-5, which means the implementation of the delivery system at PT Samudera Arkan Nusantara has been carried out but still requires regular governance processes and the results of this study found that in the PO1 and ME2 domains at PT Samudera Arkan Nusantara has met expectations, namely at level 4 Manage and Measurable but other domains still occupy level 3, namely Defined Process.